Inattention to rare events - Bartosz Maćkowiak; Mirko Wiederholt (European Central Bank (ECB), 2015)
The world recently experienced several rare events with disastrous consequences: the global financial crisis, the European sovereign debt crisis, and the Fukushima nuclear accident. These events have in common that key decision-makers were unprepared for them, which aggravated these events. We develop a model in which agents make state-contingent plans — prepare to act in different contingencies — subject to the constraint that agents can process only a finite amount of information. We identify the forces that make agents prepare little for some contingencies. We study whether a social planner would want agents to prepare more for rare events.
Keywords: D83; E58; E60; 330; disasters; efficiency; rare events; rational inattention